Environmental & architectural phenomenology. Vol. 20, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2009)
Vol. 20, No. 3, Fall 2009 (includes "items of interest," "citations received," and essays by Bernd Jager, Karsten Harries, Jeff Malpas & Edward Relph).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals